E-PUPNS DI IPDN KAMPUS KALIMANTAN BARAT - Silverius Tey Seran; Desty Pratiwi (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT This research entitled the implementation of the employees re-registration program electronically in the institute of domestic government Campus West Kalimantan. The purpose of this research is to analyze the process of implementing program of civil servant re-registration program electronically in the institution of domestic government of West Kalimantan Campus. The theory used in this research is the implementation of policy theory of Charles O. Jones. The result of the research shows that the implementation of the program of re-registration of government employees in the local government institution of the western campus of the West Kalimantan has not been done well. The reality is revealed in three aspects of the implementation process of program consisting of the organizational stage, the stage of interpretation and the application stage. Problems that arise at the organizational stage are; the main tasks and function of officers in the structure of organization is still not directed and still overlapping tasks in the field/practice. In the interpretation phase of the content and objectives of the implementation of the civil servant’s re-registration program has been understood by the verification officer, but the consistency in implementing the program implementation of the civil administration reformation program electronically as well as the implementation of monitoring and evaluation by the executing officers is not maximal yet. Although the program implementation process has not been maximal yet the initial impact of this program is very useful for civil servants in IPDN campus west Kalimantan especially in data storage of employees either in the form of physical data/hardcopy, or non physical/softcopy. Keywords: process, implementation, program, data collection, electronics